Exergetic Evaluation of a Rankine Cycle with Regeneration: Effect of Turbine Inlet Temperature and Source Temperature (2018)
The Rankine cycle is a thermodynamic cycle widely used in power plants, specifically in steam power plants, due to its great importance in the industry. It has also been studied in recent years in search of parameters that can optimize the cycle by reducing losses and thus increase efficiency, so that improvements have been made in the process such as overheating of steam at the turbine inlet, and even regeneration of water at the boiler inlet. In this work a process of optimization of a Rankine cycle was presented by complementing it with an open feed water heater which not only improves the efficiency of the cycle, but also provides a convenient means of de-aeration of the feed water to prevent corrosion in the boiler, in which it was carried out under the assumption of a stationary flow, and without significant changes in the kinetic and potential energy, that is, assuming an ideal process, all this with the aim of obtaining the highest thermal efficiency and the lowest exergetic losses in the cycle, carrying out several case studies with the assistance of Unisim with temperature variations at the turbine inlet and at the source to observe how this affects the exergetic efficiency and exergy destroyed in the turbine and it was concluded that this is reflected in the production of mechanical energy useful for creating electrical energy because a variation in these parameters could cause job losses in the turbine and decrease in the exergetic efficiency of the system which in turn would lead to a decrease in the network of the system.